2014
DOI: 10.15835/nbha4229715
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Major-to-Trace Minerals and Polyphenols in Different Apple Cultivars

Abstract: The aim of this study was to investigate the concentration level of some major-to-trace elements and toxic minerals and polyphenols (catechin, epicatechin and quercetin) in fruits belonging to different apple cultivars (‘Auriu de Cluj’, ‘Florina’, ‘Generos’, ‘Golden Delicious’, ‘Prima’, ‘Productiv de Cluj’ and ‘Starkrimson’), under specific climate conditions to northwestern Romania. The apple minerals were determined by the inductively coupled plasma mass spectrometry (ICP-MS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
9
27
3
Order By: Relevance
“…The differences between these studies can be attributed to the growth conditions, varieties, genetic factors, harvesting times, soil properties, and geographical variations (Er & Özcan, ). Our result is also comparable with the data reported by Todea et al (), Horsley, Gökbel, Özcan, Harmankaya, and Şimşek (), and Oana et al () in terms of macro and micro elements contents of apple cultivars. Furthermore, Sangwan, Kawatra, and Sehgal () compared the sun, oven, and microwave dried mint powder and found that the microwave drying method has higher results in Ca, Fe, and Cu elements than in the sun and oven drying.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The differences between these studies can be attributed to the growth conditions, varieties, genetic factors, harvesting times, soil properties, and geographical variations (Er & Özcan, ). Our result is also comparable with the data reported by Todea et al (), Horsley, Gökbel, Özcan, Harmankaya, and Şimşek (), and Oana et al () in terms of macro and micro elements contents of apple cultivars. Furthermore, Sangwan, Kawatra, and Sehgal () compared the sun, oven, and microwave dried mint powder and found that the microwave drying method has higher results in Ca, Fe, and Cu elements than in the sun and oven drying.…”
Section: Resultssupporting
confidence: 93%
“…Consequently, apple fruits may be a good source of potassium, which plays an important role in the human body, especially in the transmission process of nerve signals, but also in fluid balance and proper function of heart, muscles, kidney, and hormones (Todea et al, ). These results show that apples may be useful for the evaluation of dietary information in important food crops.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer beneficial effects of a moderate-carbohydrate (40%), high-fat (40%) calorierestricted Mediterranean diet on weight and waist circumference have been demonstrated among individuals with metabolic syndrome or more cardiovascular risk factors. Therefore, a Mediterranean diet seems a promising approach to reduce mechanical loads and thus improve OSA severity, compared to a low-fat, calorie-restricted diet (32,33).…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…Sager [9] was able to determine the main and trace element contents of tomatoes grown in Austria. Todea et al [10] have studied the level from major-to-trace elements in different apple cultivars in Romania. Abdrabo et al [11] have determined 23 elements in Spanish palm dates.…”
Section: Introductionmentioning
confidence: 99%